Occurrence of nematodes and yield of common bean and maize as a function of cropping systems under no-tillage - Loeiro da Cunha, Tatiana Pagan [UNESP]; Checchio Mingotte, Fabio Luiz [UNESP]; Chiamolera, Fernando Marcelo [UNESP]; Carmeis Filho, Antonio Carlos de Almeida [UNESP]; Martins Soares, Pedro Luiz [UNESP]; Lemos, Leandro Borges [UNESP]; Vendramini, Alaiane Regina (Organization Trop Amer Nematologists, 2015)
Nematodes are responsible for significant damage and yield suppression to common bean and maize. A possible strategy for more efficient management of these pathogens is crop rotation with non-host or nematode-antagonistic plants. The choice of plants to be used in the management of nematodes depends on knowledge of the nematode species that are present in a field and their level of infestation. The aim of this research was to evaluate the occurrence and population density of nematodes and common bean and maize yield in cultivation systems that also included Urochloa ruziziensis. The experiment was installed in a site that was naturally infested with nematodes and conducted for three years under no-tillage. The treatments consisted of cropping systems for production of straw, with maize alone, maize intercropped with U. ruziziensis, and U. ruziziensis alone (summer 2011/2012), alternating with two harvests of common bean (spring 2011 and 2012). The population of nematodes was determined from soil and roots about 80 d after sowing common bean (first and second harvests), and 104 days after sowing maize and U. ruziziensis. Common bean and maize yields were determined by threshing pods and ears contained in the entire plots. The cropping systems that included maize tended to favor population increase of Pratylenchus brachyurus and Meloidogyne incognita and lower yield of common bean. Cultivation of U. ruziziensis alone lowered the population density of P. brachyurus and M. incognita, maintaining higher common bean yield. The cultivation of maize alone or intercropping of maize and U. ruziziensis reduced the population of R. reniformis. Therefore, the inclusion of antagonistic and (or) poor host plants was necessary in these cropping systems to reduce populations of nematodes and maximize the common bean and maize yield.
Keywords: Meloidogyne incognita; Phaseolus vulgaris; Pratylenchus brachyurus; Rotylenchulus reniformis; Urochloa ruziziensis; Zea mays